Composición de los máximos cuerpos colegiados (MCC) de las universidades latinoamericanas: un análisis con base en los estatutos (2020)
The participation of stakeholders in the highest collegiate bodies (HCB) of Latin American universities is a good argument when referring to the levels of democratization of these educational institutions. Public entities, pursuant to their regulations, usually include at least internal stakeholders in their decision-making bodies, in contrast to private entities, which are characterized by having more limited participation models, since they admit only representatives of the owners of the institution in their HCB. This article intends to analyze the constitution of HCB in Latin American universities, with the purpose of creating a typology that facilitates their organization based on the greater or lesser participation of stakeholders. A sample of 220 universities that appear in the Scimago IBER 2019 classification for Latin America was used. This is a descriptive research that uses secondary sources of information (scientific articles, databases and university regulations). Overall, relationships were found between the degrees of participation and the ownership regime of the institutions with the predominance of a category called homogeneous.